Estimation of the frequency of meals consumed by children in early school age (living in Wloclawek) - Małgorzata Pujanek; Monika Anna Ameryk; Jarosław Koza; Ewa Szymelfejnik; Katarzyna Jankowska; Maciej Świątkowski (Kazimierz Wielki University, 2017)
Introduction: Adequate nutrition in children from youngest age will result in a proper physical and psychological growth. Unregular meals can cause many metabolic diseases. The important role in planning a menu plays frequency of the meals, their regularity and intervals between them. Aim: Evaluation of meal frequency among children aged 6-9 from primary schools in Włocławek. Materials and methods: The study group includes 314 children aged 6-9 randomly selected primary schools in Włocławek. The analysis was a part of a huge regional program of prevention of malnutrition, overweight and obesity by improving nutrition among children aged 6-9. The nutrition questionnaire was fullfiled by parents. The results were analyzed with computer program named Statistica 10. Results: The study showed that children from the study group made nutrition mistakes, such as insufficient numbers of meals during the day (3-4) only 70% of participants had its first meal before the school, not many more took second breakfast to the school and 25% ate junk food between meals. Ninety percent of the children had dinner and super on the regular basis. Conclusions: There is the need to change nutritional habits and make meals more regular, healthy, nutritious and diversified.